ChemInform Abstract: A Triazole Organocatalyst with Spiropyrrolidine Framework and Its Application to the Catalytic Asymmetric Addition of Nitromethane to α, β‐Unsaturated Aldehydes. Issue 17 (April 2016) - Liu, Wen‐Xing; Chen, Si‐Kai; Tian, Jin‐Miao; Tu, Yong‐Qiang; Wang, Shao‐Hua; Zhang, Fu‐Min
Abstract: A series of new water‐compatible spiropyrrolidine triazole catalysts is designed and synthesized.